(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2016)
Abstract: The interface characteristics of aluminum/cast iron bimetals produced by compound casting were investigated. Aluminum melt was poured into molds, at 700 ̊C and 750 ̊C, around cylindrical cast iron bars having melt-to-solid volume ratios (Vm/Vs) of 3, 5 and 8, respectively. Microscopic observations showed that a reaction layer may form at the interface. This layer is composed of Fe2Al5 intermetallic which has been formed initially at the notches of the insert’s surface after making contact with the molten metal. The thickness of the interaction layer varied from 5μm, for the sample produced at 700 ̊C and 3 Vm/Vs, up to 20μm for the sample poured at 750 ̊C and 8 Vm/Vs. Microstructural analysis showed that increasing of the temperature and the melt-to-solid (m/s) volume ratio leads to the formation of a thicker and more uniform intermetallic layer. Microhardness of the Fe2Al5 compound was measured 824 HV. A mechanism is suggested for the nucleation and growth of this intermetallic layer and also encapsulation of the flake graphite at the interface of two metals. It seems that the thermal and chemical situation at the interface of two metals, leads to an acceptable wettability of the graphite by molten aluminum.